Expression dynamics of metalloproteinases during mandibular bone formation: association with Myb transcription factor - Varadinkova, S.; Oralova, V.; Clarke, M.; Frampton, J.; Knopfova, L.; Lesot, H.; Bartos, P.; Matalova, E. (Frontiers in Cell and Developmental Biology, 2023)
As the dentition forms and becomes functional, the alveolar bone is remodelled. Metalloproteinases are known to contribute to this process, but new regulators are emerging and their contextualization is challenging. This applies to Myb, a transcription factor recently reported to be involved in bone development and regeneration. The regulatory effect of Myb on Mmps expression has mostly been investigated in tumorigenesis, where Myb impacted the expression of Mmp1, Mmp2, Mmp7, and Mmp9. The aim of this investigation was to evaluate the regulatory influence of the Myb on Mmps gene expression, impacting osteogenesis and mandibular bone formation. For that purpose, knock-out mouse model was used.Gene expression of bone-related Mmps and the key osteoblastic transcription factors Runx2 and Sp7 was analysed in Myb knock-out mice mandibles at the survival limit. Out of the metalloproteinases under study, Mmp13 was significantly downregulated. The impact of Myb on the expression of Mmp13 was confirmed by the overexpression of Myb in calvarial-derived cells causing upregulation of Mmp13.Expression of Mmp13 in the context of other Mmps during mandibular/alveolar bone development was followed in vivo along with Myb, Sp7 and Runx2. The most significant changes were observed in the expression of Mmp9 and Mmp13. These MMPs and MYB were further localized in situ by immunohistochemistry and were identified in pre/osteoblastic cells as well as in pre/osteocytes.In conclusion, these results provide a comprehensive insight into the expression dynamics of bone related Mmps during mandibular/alveolar bone formation and point to Myb as another potential regulator of Mmp13.